Evaluation of a PV-TEG Hybrid System Configuration for an Improved Energy Output: A Review - Saleh, Umar Abubakar; Johar, Muhammad Akmal; Jumaat, Siti Amely Binti; Rejab, Muhammad Nazri; Wan Jamaludin, Wan Akashah (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
The development of renewable energy, especially solar, is essential for meeting future energy demands. The use of a wide range of the solar spectrum through the solar cells will increase electricity generation and thereby improve energy supply. However, solar photovoltaics (PV) can only convert a portion of the spectrum into electricity. Excess solar radiation is wasted by heat, which decreases solar PV cells’ efficiency and decreases their life span. Interestingly, thermoelectric generators (TEGs) are bidirectional devices that act as heat engines, converting the excess heat into electrical energy through thermoelectric effects through when integrated with a PV. These generators also enhance device efficiency and reduce the amount of heat that solar cells dissipate. Several experiments have been carried out to improve the hybrid PV-TEG system efficiency, and some are still underway. In the present study, the photovoltaic and thermoelectric theories are reviewed. Furthermore, different hybrid system integration methods and experimental and numerical investigations in improving the efficiency of PV-TEG hybrid systems are also discussed. This paper also assesses the effect of critical parameters of PV-TEG performance and highlights possible future research topics to enhancing the literature on photovoltaic-thermoelectric generator systems.